2000
DOI: 10.4067/s0716-078x2000000400011
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversidad del complejo de artrópodos asociados al follaje de la vegetación del norte de Chile, II región

Abstract: DI > TM > TA. El contenido de cenizas de hojas y tallos también varía considerablemente y sigue el mismo patrón de variación que el contenido de agua. El contenido de nitrógeno foliar en las distintas zonas ecológicas estudiadas no varía tanto como el de agua, a excepción de TA en que son marcadamente inferiores. En cambio, en tallos es poco variable y no sigue el patrón de distribución foliar de este elemento, ni los patrones de distribución de los otros nutrientes considerados. En un enfoque global de las cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…, 1998; Squeo et al. , 1998; Luebert & Gajardo, 2000; Saiz et al. , 2000; Latorre, 2002; Latorre et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1998; Squeo et al. , 1998; Luebert & Gajardo, 2000; Saiz et al. , 2000; Latorre, 2002; Latorre et al.…”
Section: Methodsmentioning
confidence: 99%
“…Many distinct and endemic species of cacti (Copiapoa, Eulychnia) and shrubs (Gypothamniumn, Euphorbia, Nolana, Heliotropium, Sisymbrium, Bahia) occur in the unique Lomas floras. The richest and most diverse communities are found in the maximum fog zone between 600 and 800 m (Johnston, 1929;Rundel & Mahu, 1976 (Villagrán et al, 1983;Arroyo et al, 1998;Luebert & Gajardo, 2000;Saiz et al, 2000;Latorre et al, 2002).…”
Section: Climate and Vegetationmentioning
confidence: 99%
“…In neither case was there a clear relationship with water availability, and the authors concluded that range-specific climate gradients contribute to variation in species richness. In the Salar de Atacama region, Saiz et al (2000) listed higher abundance, species richness, and Shannon diversity of herbivorous arthropods in pre-Puna and Puna than in Andean steppe and Subnival zones. By contrast, Jerez (2000) found more Coleoptera species in the higher altitude vegetation belts.…”
Section: Altitudinal Patterns Of Species Richnessmentioning
confidence: 99%
“…Así por ejemplo, la riqueza específica de artrópodos epífitos en el norte de Chile (50-4100 msnm), fue mayor en lomas y quebradas cuyas condiciones orográficas e hidrográficas contrarrestan la aridez que caracteriza a las vertientes occidentales andinas en esas latitudes (Saiz et al, 2000).…”
Section: Selección De Taxones Focalesunclassified